"الأحزاب السياسية وحقوقها وموقفها في الشريعة الإسلامية والقانون اللّيبي"دراسة حالية واقعية - ام كلثوم الجيلاني العربي الأحرش
This study dealt with the subject of political parties. This study is entitled ‘Political Parties, Their Rights and Position in Islamic Sharia and Libyan Law: A Field and Current Study’. For the past 4 decades the Libyan state has never held elections and political parties also do not exist, so the understanding of political rights in Islam is different from the concept of politics found in Libyan law. But after the revolution of February 17, 2011, many drastic changes took place. The problem of the study is to identify the extent of the legitimacy of political parties according to Islamic law and Libyan law and to identify whether the political freedom guarantees each party gets their rights, especially in a situation where Libya previously practiced the concept of one party. Libya only recognized the concept of multi-party through the proclamation of the constitution on 3-8-2011. In the declaration, several rights of political parties have been stated, especially the right to form a party and the freedom of multiple parties, with the main condition that a party must not be in conflict with Islamic principles. The objective of this study is to identify whether the right to establish political parties granted by the government guarantees the rights of these political parties to move or not? And also aims to find out the obstacles that prevent political parties from exercising their rights. This study uses a descriptive historical and analytical approach as well as inference to track the emergence of political parties and their rights, analyse legal text in Islamic Jurisprudence and laws and explain the position of political parties in Islamic sharia and Libyan law, then provide commentary and interpretation. The results of the study found that the establishment of a political party should not only be legal from the point of view of Islamic law, but it also becomes a ‘fardh kifayah’, especially from the aspect of achieving benefits and rejecting harm and guaranteeing the completion of Islamic purposes to the people and ummah. Thus, the establishment of political parties in Libya is in principle not in conflict with Islamic law. However, the findings show that the permission to establish a political party still does not guarantee the freedom of political parties to exercise their rights as enshrined. Thus, researchers suggest that these constraints should be removed, the government should also take into account the sociopolitical changes of the country and clearly explain the principles of Islamic law that allow the establishment of political parties and preserve its rights in Libya. The government needs to give legal guarantees to political parties the right to establish and the freedom to exercise their rights in accordance with the law in forming a democratic state.